2020
DOI: 10.1002/biot.202000066
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Electrosynthesis—An Inventory on Technology Readiness Level and Performance of Different Process Variants

Abstract: The objective of microbial electrosynthesis (MES) is to combine the advantages of electrochemistry and biotechnology in order to produce chemicals and fuels. This combination enables resource-efficient processes by using renewable raw materials and regenerative energies. In the last decade, different MES processes have been described, for example, MES based on biofilms or mediators, electro-fermentation, and secondary MES. This review compares the MES technologies with regard to the reached process performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…The exact way of how the cells metabolism is influenced by EF is not well known. However, it is known that various metabolic processes that compete for reducing power from the NADH/NAD + pool, can adversely affect the 1,3-propanediol production yield in glycerol fermentation [84]. Zhou and coworkers demonstrated that the use of an electrode to provide additional reducing equivalents resulted in an improvement of 25% (1 mM-4 mM) on 1,3-propanediol production possibly due to the enhance of NADH generation routes [85].…”
Section: Added-value Biochemicals Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact way of how the cells metabolism is influenced by EF is not well known. However, it is known that various metabolic processes that compete for reducing power from the NADH/NAD + pool, can adversely affect the 1,3-propanediol production yield in glycerol fermentation [84]. Zhou and coworkers demonstrated that the use of an electrode to provide additional reducing equivalents resulted in an improvement of 25% (1 mM-4 mM) on 1,3-propanediol production possibly due to the enhance of NADH generation routes [85].…”
Section: Added-value Biochemicals Productionmentioning
confidence: 99%
“…Zhou and coworkers demonstrated that the use of an electrode to provide additional reducing equivalents resulted in an improvement of 25% (1 mM-4 mM) on 1,3-propanediol production possibly due to the enhance of NADH generation routes [85]. The applied potential can impact the microbial population structure and also selects the microbial community composition on the electrode's surfaces influencing the intracellular redox regulations [83,84].…”
Section: Added-value Biochemicals Productionmentioning
confidence: 99%
“…Heavily as industry has grown to depend on microorganisms, only one in 5000-10 000 biotechnology innovations derived from academia survives the long route from the initial findings to product commercialization [5]. Generally referred to as the 'Valley of Death' [6], the division between innovation and application starts at the different product development levels at which academia and industry operate, known as technology readiness levels (TRLs) [7]: typically TRL 1-3 in academia and TRL 8 and 9 in industry. At TRL 4-7, the discovery process is generally considered too applied for further scientific funding but too risky to fund for industrial market implementation.…”
Section: The Rise Of Biotechnologymentioning
confidence: 99%
“…Alternatively, changes in the composition of the microbial community could also help. Intermixing of cultures or creating co-cultures can be used in biofilm-based MES to enhance the performance of the system as these cultures are robust to changes in the environment and are flexible with different types of substrates [65]. However, when present in abundant quantity, the species compete with one another for e − , leading to a decrease in the product specificity [66].…”
Section: Electrosynthesis Assisted By Microbesmentioning
confidence: 99%
“…A potential solution for the same is enriching specific species by using electrochemically-driven reactions in the long run, along with the addition of supplements. Biofilm-based MES highlighting the different process performances have been explained by Fruehauf [65].…”
Section: Electrosynthesis Assisted By Microbesmentioning
confidence: 99%